Does growth cause structural change, or is it the other way round?: a dynamic panel data analyses for seven OECD countries - Andreas Dietrich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In economic development, structural change among the three main sectors of an economy accompanies with aggregate economic growth. Nevertheless the question whether economic growth causes structural change or change in the economic structure causes aggregate growth is still unanswered. To shed some more light on this issue, this study examines a Grangercausality test in a panel environment to determine the causality of economic growth and structural change measured either in terms of employment shares or in terms of real value added shares. Estimation and analysis with annual data of seven OECD countries covering the period from 1960-2004 show that the causality appears to be heterogeneous.
Keywords: L16; O14; O57; 330; Structural change; economic growth; tertiarization; panel Granger-causality-test; Strukturwandel; Wirtschaftswachstum; Panel; Kausalanalyse; Drei-Sektoren-Hypothese; Schätzung; OECD-Staaten